Social network factors affecting adoption of Mobile app by farmers - NIKAM, VINAYAK; KUMAR, SHIV; M, KINGSLY I (The Indian Journal of Agricultural Sciences, 2021)
Effect of social network on adoption of Mobile app was studied in Nashik and Sangli districts of Maharashtra, India by interviewing 800 grape growers during 2016-17. Individual characteristics like income, landholding, caste, area under grapes and number of smartphones were significant factors determining the adoption of mobile app. In social network factors, village adoption rate, membership, education, landholding and frequency of communication were significant determinants of adoption. Village adoption rate of the technology resembles network behavior. Therefore, both social network characteristics and social network behavior influences the adoption decision of farmers. It shows that adoption is not just mimicking by the farmers, but it is a social learning process. The results emanating from the study provide insights to extension agents to devise strategy for introduction of any technology/ICT in agriculture. The way out to implement the strategy is to use extension methods that focus on social learning like Farmers Field Schools; target the farmers having more education, landholdings and who frequently interact with the large number of farmers to facilitate and enhance the adoption of new technology/ICT.